OSCE's Resilience in Times of War - Jelena Cupać (Polarization, Shifting Borders and Liquid Governance: Studies on Transformation and Development in the OSCE Region, 2024)
With Russia's invasion of Ukraine in 2022 and the subsequent war between two of its core participating states, the OSCE seems highly fragile, and many doubt it will survive. However, this paradigm needs to follow an assessment of the OSCE's resilience in times of crisis, grounded in International Relations research on international organizations. This chapter seeks to fill this gap, hoping to find a new perspective on what the OSCE can do to survive the Ukrainian war and remain relevant in the long term. To that end, it assesses the OSCE's resilience using formal factors such as its issue area, membership, age, and the quality of its bureaucracy. The chapter also adopts a historical perspective, which evaluates the OSCE's resilience through its relationship with the post-Cold War security environment. This perspective suggests that the OSCE might be more resilient than formal organizational factors indicate. Overall, assessing the OSCE's resilience from these two perspectives calls for more optimism about its future amid the war in Ukraine. However, it also indicates that the likely price of the OSCE's survival will~be its contraction to a forum in which normative conflicts prevail over compromise.
Keywords: 300; OSCE; Organizational resilience; Ukrainian war; Russia